Dietary Intervention in Hypertension: Mechanisms, Efficacy, and Future Directions - Tri Tjahjono, Cholid; Arthamin, Maimun; Prakosa, Ardani; Insanitaqwa, Aleyda (Universitas Brawijaya, 2025)
Hypertension significantly contributes to global cardiovascular morbidity and mortality, with diet being a key modifiable factor in its management. Evidence supports the effectiveness of dietary approaches including the Mediterranean, low-sodium, DASH, and plant-based diets in lowering blood pressure and enhancing cardiovascular health. These benefits are mediated by mechanisms including improved electrolyte balance, minimized oxidative stress, enhanced nitric oxide bioavailability, and favorable modulation of neurohormonal pathways. Despite strong evidence, long-term adherence is hindered by cultural food preferences, limited access to healthy options, and socioeconomic disparities. Emerging approaches, including personalized nutrition, digital health tools, and culturally adapted meal planning, show promise in overcoming these barriers. Additionally, recent insights into nutrient bioavailability, gut microbiota interactions, and gene-diet relationships are reshaping the future of dietary intervention strategies. To maximize impact, healthcare providers must take an active role in delivering tailored dietary guidance as part of routine hypertension care. Multidisciplinary collaboration and community engagement are critical for translating evidence into sustainable practice. Overall, emphasizing diet as a therapeutic tool offers an opportunity to shift the paradigm of hypertension management toward prevention, personalization, and long-term cardiovascular health.